Continuously efficient hydrodeoxygenation of glycerol into 1, 3-propanediol over Pt/WOx/beta catalysts. Issue 6 (23rd February 2021) - Zhu, Lijun; Sun, Mengya; Zhao, Xinpeng; Zhang, Yanfei; Luo, Hu; Liu, Wang; Miao, Gai; Kong, Lingzhao
Abstract : Continuous hydrodeoxygenation of glycerol into 1, 3-PDO for over 600 h was attributed to the highly dispersed metals without aggregation on a Pt/WO x /beta catalyst. Abstract : The efficient and continuous hydrodeoxygenation (HDO) of glycerol into 1, 3-propanediol (1, 3-PDO) in a trickle bed reactor at 160 °C over Pt/WO x /beta catalyst was developed. XRD, XPS, UV-Vis DRS, HAADF-STEM, ICP, and DRIFT analyses indicated that the synthesized catalyst with 1.5 wt% Pt and 0.5 wt% W exhibited satisfactory dispersion of metals within 2.0 nm particle size due to the strong interactions between metals and support. With 1.0 h −1 of weight hourly space velocity (WHSV) and 500 g L −1 glycerol, the selectivity of 1, 3-PDO and n -PrOH were 51.3% and 32.1%, which corresponded to their space-time yield (STY) values of 2.5 g gPt −1 h −1 and 1.5 g gPt −1 h −1, respectively. After 600 h of stable and continuous running, the Pt/WO x /beta catalyst still maintained good activity, which was attributed to the highly dispersed metals without aggregation. There was satisfactory consistency between the proposed kinetic parameters for glycerol consumption, and 1, 3-PDO and n -PrOH formation and the actual HDO results.